Inovasi Pelayanan Publik melalui Aplikasi “Pantai Balikpapan” oleh Dinas Kependudukan Dan Pencatatan Sipil Kota Balikpapan - Jihan Fadhila; Muhammad Jamal (Jurnal Ilmu Pemerintahan, 2023)
This research aims to understand and describe the online-based innovation of Pantai Balikpapan conducted by the Department of Population and Civil Registration of Balikpapan City. It also aims to identify the inhibiting and supporting factors in the implementation of the Pantai Balikpapan innovation at the Department of Population and Civil Registration of Balikpapan City. The research results indicate that the Public Service Innovation through the "Pantai Balikpapan" Application at the Department of Population and Civil Registration of Balikpapan City, based on Rogers' theory (2003) that suggests relative advantage indicators providing many benefits for application users, can be seen in terms of budget savings and faster processing time that can be done at home. Pantai Balikpapan Innovation aligns with the needs of the community, and users find it easy to operate without complexities. Prior to the deployment of the Pantai Balikpapan Innovation, trials and socialization were conducted to the public.Pantai Balikpapanis easily accessible and observable by the public, anytime and anywhere. The supporting factor in implementing online services is having sufficient human resources and adequate equipment. However, the inhibiting factors in this public service innovation include network disruptions and uneven socialization.